Read to death. - Moran, Terrie Farley (Moran, Terrie Farley. Read 'Em and Eat mystery., 2016)
With their book club season wrapping up with The Florida Life of Thomas Edison, Sassy and Bridgy decide to take their group on a day-trip to the beautiful Edison and Ford Winter Estates. Hiring driver Oscar Frieland, who's known for his colorful stories and love of the café's Robert Frost fruit tartlets, the bibliophiles set off for a day of sunshine and history. After a lovely excursion, the club returns to the café for lunch and a book discussion, but the group falls silent after Oscar is found dead in his van. The sheriff's deputies have some questions of their own for the group, and if the ladies don't find some answers soon, the next book they read might be from a prison library.